Bile Acids, FXR, and Metabolic Effects of Bariatric Surgery - Olivier F. Noel; Christopher D. Still; George Argyropoulos; Michael Edwards; Glenn S. Gerhard (Journal of Obesity)
Overweight and obesity represent major risk factors for diabetes and related metabolic diseases. Obesity is associated with a chronic and progressive inflammatory response leading to the development of insulin resistance and type 2 diabetes (T2D) mellitus, although the precise mechanism mediating this inflammatory process remains poorly understood. The most effective intervention for the treatment of obesity, bariatric surgery, leads to glucose normalization and remission of T2D. Recent work in both clinical studies and animal models supports bile acids (BAs) as key mediators of these effects. BAs are involved in lipid and glucose homeostasis primarily via the farnesoid X receptor (FXR) transcription factor. BAs are also involved in regulating genes involved in inflammation, obesity, and lipid metabolism. Here, we review the novel role of BAs in bariatric surgery and the intersection between BAs and immune, obesity, weight loss, and lipid metabolism genes.